The Quality of Child Identity Card (KIA) Services During the Covid-19 Pandemic at the Population and Civil Registration Office of Lebong Regency - Vevi Novita (International Journal Labs, 2023)
Indonesia is one of the fourth most populous countries in the world with a large population at this time. It is not wrong that Indonesia is designated with the fourth largest population in the world, so that Indonesian citizens deserve protection, recognition, and legal certainty. The purpose of this study was to determine the quality of Child Identity Card (KIA) services during the Covid-19 Pandemic at the Population and Civil Registration Office of Lebong Regency. In this study, the type of research approach used is a qualitative approach. The quality of Child Identity Card (KIA) services during the Covid-19 pandemic at the Lebong Regency Population and Civil Registration Office in 2021 is based on service quality indicators consisting of 5 indicators, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy dimensions. As the first indicator of service quality, service support facilities at the Population and Civil Registration Office of Lebong Regency are still inadequate and have not satisfied the community. Overall in this indicator is quite good, careful and precise in providing services, has Standard Operating Procedures and is also able to control supporting equipment.